Medical students' attitudes to mental illnesses and to psychiatry before and after the psychiatric clerkship: Training in a specialty and a general hospital. (December 2017) - Economou, Marina; Kontoangelos, Kontantinos; Peppou, Lily Evangelia; Arvaniti, Aikaterini; Samakouri, Maria; Douzenis, Athanasios; Papadimitriou, George N.
Abstract: Medical students' attitudes to mental illnesses and psychiatry may be reshaped during the psychiatric training, with important implications in their future practice of the profession. Therefore, the present study set out to explore the impact of the psychiatric clerkship in students' attitudes, while taking into consideration the site of their practical training. To this end, a total of 678 final-year medical students were recruited. Students completed a self-reported questionnaire entailing the Attitudes to Psychiatry scale, the Attitudes to Mental Illness scale and the Greek Social Distance scale before and after their placement. Findings indicate that the psychiatric clerkship had a positive effect in reducing stigma towards both psychiatry and mental illnesses, with the effect being more pronounced in the general hospital with respect to the former, while in the specialty hospital was more marked regarding the latter. A further exploration of the determinants of change revealed that the improvement discerned in the general hospital was only among those without professional experience of mental illnesses. Therefore, the psychiatric clerkship may exert a substantial influence on shaping favourable attitudes towards mental illnesses and psychiatry; however, other elements should also be taken into consideration, if the clerkship is to tackle stigma in healthcare. Highlights: The psychiatric clerkship improves attitudes to mental illnesses and psychiatry. Training in a general hospital primarily improves attitudes to psychiatry. Training in a specialty hospital primarily improves attitudes to mental illnesses. Tackling stigma in health care necessitates stressing a bio-psychosocial approach.